Faktor-Faktor yang Berhubungan dengan Fungsi Staffing Kepala Ruangan Berdasarkan Persepsi Perawat di Rsud dr. H. M. Rabain Muara Enim - Serly Agustina; Mira Asmirajati; Oyoh Oyoh; Iin Inayah; Setiawati Setiawati (Universitas Pahlawan Tuanku Tambusai, 2025)
The implementation of the staffing function by the head nurse has not been carried out optimally. This affects the effectiveness of nursing care delivery. One indication of this is the placement of nursing staff that is not based on an evaluation of actual needs and individual competencies.The purpose of this study was to analyze the factors related to the head nursing’s staffing function at Dr. H. M. Rabain Muara Enim Regional Hospital. This study is a descriptive analytical study where this study uses a survey method with a Cross Sectional design. The sample in this study were nurses working at Dr. H. M. Rabain Muara Enim Regional Hospital with a sample size of 177 nurses. This study used a questionnaire instrument in collecting data. The data analysis used was the chi square test for bivariate and multiple logistic regression analysis for multivariate. The results of the study showed that the planning function (pvalue 0.001), recruitment (pvalue 0.007), orientation (pvalue 0.016), placement (pvalue 0.019), training (pvalue 0.003), performance (pvalue 0.00), and knowledge (pvalue 0.005) affect the staffing function of the ward head. The performance factor is the most dominant factor that affects the staffing function of the ward head (B 5.626). The results of this study can be used as a consideration for hospitals in managing the staffing function of the ward head, especially in assessing nurse performance so that it is expected to support the achievement of hospital goals and the provision of complete health services. It is recommended that ward heads improve their staffing functions and hospitals provide additional training on ward head management. In addition, the nursing management department and ward heads can evaluate the criteria and indicators for assessing nurse performance considering the importance of performance assessment.